2016
DOI: 10.1128/genomea.01281-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Mycobacterium Phage Waterfoul

Abstract: Waterfoul is a newly isolated temperate siphovirus of Mycobacterium smegmatis mc2155. It was identified as a member of the K5 cluster of Mycobacterium phages and has a 61,248-bp genome with 95 predicted genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Here, we report the results of a genome-wide overexpression screen of the complete set of genes encoded by a single mycobacteriophage. Phage Waterfoul is a temperate siphovirus isolated on M. smegmatis mc 2 155 ( Jackson et al 2016 ). Based on gene content similarity, Waterfoul is part of phage cluster K ( Russell and Hatfull 2017 ), which includes several members that have been shown to infect clinically important strains of mycobacteria ( Pope et al 2011 ; Jacobs-Sera et al 2012 ; Dedrick et al 2019a , 2021 ; Guerrero-Bustamante et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report the results of a genome-wide overexpression screen of the complete set of genes encoded by a single mycobacteriophage. Phage Waterfoul is a temperate siphovirus isolated on M. smegmatis mc 2 155 ( Jackson et al 2016 ). Based on gene content similarity, Waterfoul is part of phage cluster K ( Russell and Hatfull 2017 ), which includes several members that have been shown to infect clinically important strains of mycobacteria ( Pope et al 2011 ; Jacobs-Sera et al 2012 ; Dedrick et al 2019a , 2021 ; Guerrero-Bustamante et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Waterfoul encodes 94 predicted protein-coding genes and a single predicted tRNA(Trp) ( Fig. 1 ), and as is typical for phage genomes, most genes (∼60%) have no assigned functions ( Jackson et al 2016 ; Russell and Hatfull 2017 ). In our study, a diverse set of 32 Waterfoul genes were found to be cytotoxic when expressed from a multi-copy plasmid in the host bacterium M. smegmatis , including 17 NKF genes and several genes with predicted core viral functions.…”
Section: Introductionmentioning
confidence: 99%